Absent friends [compact disc, unabridged] - Rozan, S. J. (BBC Audiobooks America, 2004)
The secrets of a group of childhood friends unravel in this haunting thriller by Edgar Award winner S. J. Rozan. Set in New York in the unforgettable aftermath of September 11, Absent Friends brilliantly captures a time and place unlike any other, as it winds through the wounded streets of New York and Staten Island...and into a maze of old crimes, damaged lives, and heartbreaking revelations. The result is not only an electrifying mystery and a riveting piece of storytelling but an elegiac novel that powerfully explores a world changed forever on a clear September morning. In a novel that will catch you off guard at every turn, and one that is guaranteed to become a classic, S. J. Rozan masterfully ratchets up the tension one revelation at a time as she dares you to ponder the bonds of friendship, the meaning of truth, and the stuff of heroism.